Minimizing seepage in irrigation canals in land reclamation systems via an innovative technology - Kalybekova, Yessenkul; Zhu, Kai; Nurlan, Balgabaev; Seytassanov, Ibragim; Ishangaliyev, Timurlan; Yermek, Auyelbek; Ismailova, Gauharkul; Kurmanbek, Zhanymhan; Issakov, Yerlan; Dávid, Lóránt Dénes (Frontiers in Sustainable Food Systems, 2023)
The escalating demand for water and the impact of climate change are posing significant challenges to global water scarcity and agricultural policies. The aim of this research is to investigate the factors influencing water losses in irrigation systems and provide recommendations to minimize such losses. The research methodology includes conducting studies to identify the factors causing water losses through evaporation and seepage from irrigation canals in the Kazakh part of the Ile River basin. The research results are theoretically substantiated, and a series of field studies are carried out at the interfarm canal experimental site in Almaty province. Based on the factors affecting evaporation and seepage losses in irrigation canals, a new design of irrigation canal made from geocomposite material has been developed and introduced. This design helps to prevent water losses in inter-farm and onfarm canals of reclamation systems. The geocomposite polymer troughs have improved the technical level of irrigation systems and have enabled additional irrigation areas by increasing the efficiency of